MSME MARKETING STRATEGY IN THE COVID-19 PANDEMIC OUTBREAK (CASE STUDY IN ANDALAS STEAK BANDAR LAMPUNG) - Noorikha Pandayahesti Saputeri; Eki Tiyas Nurulia; Warsiyah Warsiyah; Nina Ramadhani Wulandari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Based on the results of observations, the average MSME felt a decrease in turnover during the Covid-19 pandemic. This happens because of the reduced activities carried out outside the home, difficulties in obtaining raw materials due to transportation constraints, and the decline in public confidence in products that are outside the home. Another finding based on observations, not all MSMEs have to close their businesses, some MSMEs still survive despite experiencing a decline in sales turnover. As well as making products adjustments and carrying out several marketing strategies to maintain their business. This research aims to find out what marketing strategy is applied by Andalas Steak SMEs during the covid-19 pandemic, the obstacles faced, and the solutions for Andalas Steak. This is descriptive research with a qualitative approach. The descriptive qualitative method was chosen because the research carried out was related to ongoing events and related to current conditions. The results showed that Andalas Steak exerts the 4P Marketing Mix which consists of a product strategy, a price strategy, a promotion strategy, and a place strategy. The obstacles faced by Andalas Steak are a lot of competition with the same menu and people's purchasing power has decreased due to the declining economy. To counter those hindrances, Andalas Steak enforces healthy cash flow, maximizes social media, maximizes delivery services, and improves product quality and innovation.